The Role of Parents During the Covid-19 Pandemic in Children's Learning Process at Home - Pertiwi, Annisa; Perdana Prasetya, Eska (Universitas Ibn Khaldun, 2023)
This study was conducted to determine the role of parents in accompanying children during the learning process at home during the covid-19 pandemic and to determine the obstacles and supporting factors that affect the child's learning process during the covid-19 pandemic by using qualitative research methods with a data collection process through interviews and descriptive data analysis. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results showed that (1) the role of parents in the learning process at home during the pandemic in educating children includes mentoring and as motivators. (2) supporting factors obtained from places that facilitate children's learning in RA Nurul Ilmi Cibeling, as well as parents who facilitate the involvement of learning activities in early childhood education in RA Nurul Ilmi Cibeling Bogor Regency.